Antigen Presentation by Dendritic Cells after Immunization with DNA Encoding a Major Histocompatibility Complex Class II–restricted Viral Epitope - Casares, Sofia (The Rockefeller University Press, 1997)
Intramuscular and intracutaneous immunization with naked DNA can vaccinate animals to the encoded proteins, but the underlying mechanisms of antigen presentation are unclear. We used DNA that encodes an A/PR/8/34 influenza peptide for CD4 T cells and that elicits protective antiviral immunity. DNA-transfected, cultured muscle cells released the influenza polypeptide, which then could be presented on the major histocompatibility complex class II molecules of dendritic cells. When DNA was injected into muscles or skin, and antigen-presenting cells were isolated from either the draining lymph nodes or the skin, dendritic, but not B, cells presented antigen to T cells and carried plasmid DNA. We suggest that the uptake of DNA and/or the protein expressed by dendritic cells triggers immune responses to DNA vaccines.